Management affecting Quality management principles of Small and Medium Enterprises in Bangkok - Linje, Chalida (Arts of Management Journal, 2020)
The purposes of this research were to study the management that affected the quality management principles of the Small and Medium Enterprises in Bangkok. The sample used in the study was 402 from population 420 people in the Small and Medium Enterprises in Bangkok. The study was a quantitative research. The instruments used were questionnaires, using descriptive statistics; frequency, percentage, mean, standard deviation. And correlation analysis of variables with Pearson correlation coefficients. The results of study found that the Small and Medium Enterprises in Bangkok were opinions toward the quality management of Small and Medium Enterprises in Bangkok, over all were at high levels. When considering each aspect, found that; there was at high level in all aspects. And the strategic management by 7s McKinsey, found that the Small and Medium Enterprises in Bangkok, their opinions on the strategy’s management by 7s McKinsey were at high levels. When considering each aspect, found that; there was at high level in all aspects. The correlation of strategic management by McKinsey 7s toward the Quality Management Principles of Small and Medium Enterprises in Bangkok, the correlation was in the same direction. The correlation was at high level with the statistically significant at 0.05 level. Problems and barriers of quality management principles of the Certified Accounting Practice Office in Thailand, they due to shortage of accountants and lack of self-development in training to increase their skills, knowledge, abilities, expertise and language skills.